Islamic Knowledge Authority in the Virtual Space: Between Inclusivism and Exclusivism for Library Users UIN Sunan Ampel Surabaya - Hamidah, Aries (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Islamic authority continues into the era of information technology development, the most striking thing is the shift in authority in the current era. Virtual space has become a connecting bridge and producer of religious knowledge for Muslims. Every Muslim is their own authority, Muslims produce their religious understanding on each of their social media accounts. The question is whether religion in virtual spaces has lost its prominence in religious knowledge, or has this virtual world become a platform for spreading inclusive teachings. This research uses qualitative methods, by taking field data and then processing it with several theoretical perspectives. The result of the study in this research is that the presence of virtual space has given rise to a new typology of Islamic authority within the academic scope of UIN Sunan Ampel, namely virtual world Islamic authority